Managerial accounting - Sollenberger, Harold M.; Schneider, Arnold (Cincinnati, OH : South-Western College, 1996)
This book is divided into five parts: Managerial accounting framework; Product cost framework; Planning and control framework; Decision-Making framework; and Extensions in managerial analysis.
Keywords: Accounting; Managerial accounting; Cost accounting